THE ROLE OF WOMEN IN DOMESTIC WASTE MANAGEMENT BASED ON â4PâPROGRAM AT COASTAL REGION LABUHAN HAJI VILLAGE- EAST LOMBOK - Susilowati, Lolita Endang (Jurnal Lembaga Penelitian Universitas Mataram, 2014)
Domestic waste is closely associated with cleanliness, health, aesthetics and safety. Women are responsible for all of these . The purpose of this study was to describe the womenâs role in the domestic waste management based on the â4 Pâ program (sorting, processing, utilizing and residue disposal). The descriptive research method was used in this study. Survey was conducted to 15 respondents of the Mandar village by means of the purposive sampling method. The respondents were housewife aged 17-50 years. The study results showed that the average amount of the domestic waste produced was about 0.5kg/person/day. The waste composition was 85% of organic and the remaining was plastics, glasses, cans and others. Womens social and economic status in the area is relatively low in terms of education, income and occupation. Most women on thisÂ  area had not applied the â4Pâ program. Waste sorting was only undertaken for the purpose of sale. The higher the social-economic status of women, the better the manage waste. In conclusion, the role of the housewife in managing domestic waste based on the â4 Pâ program hasÂ  not been done perfectly.Therefore, structured education and training about the program is needed to establishÂ  good behavior in waste management